Coexisting Frailty, Cognitive Impairment, and Heart Failure: Implications for Clinical Care - Butts, Brittany (J Clin Outcomes Manag, 2015)
OBJECTIVE: To review some of the proposed pathways that increase frailty risk in older persons with heart failure and to discuss tools that may be used to assess for changes in physical and cognitive functioning in this population in order to assist with appropriate and timely intervention. METHODS: Review of the literature. RESULTS: Heart failure is the only cardiovascular disease that is increasing by epidemic proportions, largely due to an aging society and therapeutic advances in disease management. Because heart failure is largely a cardiogeriatric syndrome, age-related syndromes such as frailty and cognitive impairment are common in heart failure patients. Compared with age-matched counterparts, older adults with heart failure 4 to 6 times more likely to be frail or cognitively impaired. The reason for the high prevalence of frailty and cognitive impairment in this population is not well known but may likely reflect the synergistic effects of heart failure and aging, which may heighten vulnerability to stressors and accelerate loss of physiologic reserve. Despite the high prevalence of frailty and cognitive impairment in the heart failure population, these conditions are not routinely screened for in clinical practice settings and guidelines on optimal assessment strategies are lacking. CONCLUSION: Persons with heart failure are at an increased risk for frailty, which may worsen symptoms, impair self-management, and lead to worse heart failure outcomes. Early detection of frailty and cognitive impairment may be an opportunity for intervention and a key strategy for improving clinical outcomes in older adults with heart failure.